A new approach to monetary theory and policy: a monetary theory of value - Abdullah, Adam (IDOSI Publications, 2014)
This paper seeks to establish whether the Malaysian ringgit, as a fiat currency, satisfies the store of value function of money. Since the collapse of the gold standard, the migration of the medium of exchange from a commodity standard to fiat money backed by debt, has not only resulted in a significant decay in intrinsic value but also involves a transfer of wealth. This necessarily requires a re-appraisal of modern monetary theories that have influenced policy makers, but also explains the effect of such policies through analysis of macroeconomic variables on price stability. This paper presents an alternative monetary policy, which targets the stable value of currency to generate price stability over the long term and hence sustain economic growth.